2008
DOI: 10.1007/s10549-008-9893-8
|View full text |Cite
|
Sign up to set email alerts
|

HER2 in well differentiated breast cancer: is testing necessary?

Abstract: Given the low rate of well differentiated HER2 positive tumors, falling within the range reported for false negative IHC tests for HER2, and the absence of published data demonstrating a beneficial effect of trastuzumab therapy in this subset of patients, HER2 testing should not be considered a standard of care for all patients with well-differentiated breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Development of a rational approach to selecting cases for HER2 testing would promote cost effectiveness in the health care system [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Development of a rational approach to selecting cases for HER2 testing would promote cost effectiveness in the health care system [25]. …”
Section: Introductionmentioning
confidence: 99%
“…All cases had been reported as nuclear grade 1 and/or modified Scarf–Bloom Richardson (SBR) grade 1. The grading systems utilized were not standardized among the study sites, and review of slides was not performed to confirm tumour grade or HER2 IHC status . The authors concluded that as the rate of HER2 positivity in well‐differentiated breast cancer is extremely low, elimination of routine HER2 testing for this subset should be considered …”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true of Nottingham grade 3 tumours, as HER2 amplification is more likely to be demonstrated in this group. In the setting of well‐differentiated carcinomas, however, interpretation of the HER2 IHC as equivocal can be more challenging, given the necessity of an expensive reflex test coupled with the knowledge that such tumours are rarely HER2 amplified . Adding to the interpretive difficulty is the fact that many of these cases have ‘weak’ or ‘borderline’ equivocal features, some of which might be categorized differently depending on the definition of 2+ HER2 IHC used and because of interobserver variability .…”
Section: Introductionmentioning
confidence: 99%
“…This process occurs through the binding of the Par6 and atypical protein kinase C (Par6-aPKC) components of the Par complex upon HER2 activation [ 37 ]. Thus, HER2(+) tumours are poorly differentiated [ 36 , 39 ]. Amplification of the HER2 gene, located on chromosome 17 (17q12q21), leads to the overexpression of HER2 receptors and is highly associated with increased cell proliferation, tumorigenesis and invasion, resulting in distant metastases [ 33 , 40 ].…”
Section: Her2 Breast Cancermentioning
confidence: 99%